Harmonisasi Paksa Siwa Dan Paksa Budha Di Bali (Perspektif Teologi Kontekstual) - I Nyoman Kiriana (Jayapangus Press, 2021)
This article is the result of qualitative research using hybridity theory and the concept of the Siwa-Buddha theology (I Gusti Bagus Sugriwa). Hinduism and Buddhism are one of the religions found in Indonesia and initially developed and was born in India. Even so, the existence of these two religions is disharmonious in the land of their birth. The problem studied is the factors that cause Siwa-Buddha to coexist harmoniously in Bali. The method used in this research is a qualitative method with an interfretative paradigm. The object of his study is the harmonization of Śiwa and Buddha in Bali. The result and discussion is that the factors that cause Śiwa-Buddha Coexistence in Bali include theological, philosophical, historical, psychological and sociological factors. (1) The telogical factor of Siwa teachings is manifested by the symbol of Ongkara, while in Budha it is called Hrih. (2) The philosophical factor of Śiwa-Buddha harmony in Bali in the concept of deliverance in Hindu religious beliefs will lead to the realm of Sūnya and Nirvana in Budha beliefs. (3) Historical factors in the area of ​​origin Siwa-Buddha experienced great conflict and became a dark historical record, but in Indonesia on the contrary Siwa-Buddha lived in harmony and hamonis. (4) The psychological factor of tantric Śiwa-Buddha teachings, the human body as a miniature universe it becomes the center of a quest to the One through the use of Aksara, Mantra, Yantra, Mudra, and Yoga. (5) The sociological factors of the Balinese Hindu community are familiar with that Śiwa-Budha are indeed one and One. Bhatara Śiwa-Buddha withtraits Ardhanareswari in Bali is known as Hyang Tunggal. The existence of Śiwa-Buddha in Bali, which is a meeting between two beliefs and can live side by side and in harmony in Bali.